(3GdeMGSHI GdVQjHjIs - (3efUhQ(B, (3GdHOjhjs; (3Cjef TJjhj(B, s ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2010)
(3jVe adSaI bGfhf GdVQjHI Ydi GdONd Qbe(B91 (3dSfI (B2005(3, GdVQjHI Ydi GdeQJHGJ, GdGWGQ GdfXQj ddVQjHI GdYGeI Ydi GdeHjYGJs
Keywords: (3GdVQGFH(B- (3GdeMGSHIs; (3VQGFH GdONds; (3VQGFH GdONd(B- (3eMGSHIs